Bagaimana Orientasi & Pelatihan mendorong Niat untuk Melanjutkan sebagai Relawan? Persepktif Social Learning Theory - Supriharyanti, Elisabeth; Pradana, Dominicus Wahyu; Tiala, Agustinus Lengga; Stanley, Stanley; Immaniar, Paquita (Universitas Negeri Malang, 2023)
Abstract : based on social learning theory, this paper examines the relationship between orientation and training, volunteer-organization fit and intention to continue as a volunteer. This paper also investigates whether tenure as a volunteer affects orientation and training relationship intention to continue as a volunteer. This study uses cross-sectional data from various non-profit organizations. Using Google form, data was collected through questionnaires from 188 volunteers from non-profit organizations. According to the analysis results using SEM-PLS, orientation and training positively influenced intention to continue as a volunteer mediated by volunteer-organizational fit. Meanwhile, tenure moderates the influence of orientation and training on intention to continue as a volunteer. The author examines the effect of orientation and training on intention to continue as a volunteer through the mediating role of a volunteer-organization fit, for which empirical studies are still limited. The results of this paper expand on the existing literature by providing evidence from Indonesia and practical implications. Keywords: Training management, Volunteer-organization Fit, Intention to continue, Volunteers, Non-profit organizations Abstrak : berdasarkan teori pembelajaran sosial, makalah ini mengkaji hubungan antara orientasi dan pelatihan, kecocokan organisasi-relawan dan niat untuk melanjutkan sebagai relawan. Makalah ini juga menyelidiki apakah masa jabatan sebagai relawan mempengaruhi hubungan orientasi dan pelatihan terhadap niat untuk melanjutkan sebagai relawan. Studi ini menggunakan data cross-sectional dari berbagai organisasi nirlaba. Menggunakan formulir Google, data dikumpulkan melalui kuesioner dari 188 sukarelawan dari organisasi nirlaba. Menurut hasil analisis menggunakan SEM-PLS, orientasi dan pelatihan berpengaruh positif terhadap niat untuk melanjutkan sebagai relawan yang dimediasi oleh kecocokan organisasi-sukarelawan. Sementara itu, masa jabatan memoderasi pengaruh orientasi dan pelatihan terhadap niat untuk terus menjadi relawan. Penulis mengkaji pengaruh orientasi dan pelatihan terhadap niat untuk melanjutkan sebagai relawan melalui peran mediasi kecocokan organisasi-sukarelawan, yang studi empirisnya masih terbatas. Hasil makalah ini memperluas literatur yang ada dengan memberikan bukti dari Indonesia dan implikasi praktis.Kata kunci: Manajemen pelatihan, Volunteer-organization Fit, Niat untuk melanjutkan, Relawan, Organisasi nirlaba